Prevention of wrong-level surgery in the thoracic spine: preoperative computer tomography fluoroscopy-guided percutaneous gold fiducial marker placement in 57 patients - Ishak, Basem; Abdul-Jabbar, Amir; Tawfik, Tamir; Yilmaz, Emre; von Glinski, Alexander; Unterberg, Andreas; Oskouian, Rod; Chapman, Jens R. (Spine, 2020)
Study Design. Retrospective review. Objective. The aim of this study was to evaluate the feasibility, safety,s and complications of computer tomography (CT) fluoroscopy-guided percutaneous transpedicular gold fiducial marker insertion to reduce incidence of wrong-level surgery in the thoracic spine. Summary of Background Data. Intraoperative localization of the correct thoracic level can be challenging and time-consuming, especially in obese patients and patients with anatomical variations. In the literature there are very few studies containing low numbers of patients which assessed CT or CT fluoroscopy-guided fiducial marker placement of the thoracic spine. Description of this technique has been similarly scarce. Methods. All patients who underwent percutaneous CT fluoroscopy-guided gold fiducial marker placement of the thoracic spine were retrospectively reviewed. Indications for surgery included degenerative disc disease, infection, spinal metastasis, and intra- and extradural tumors. Gold fiducial markers were placed using a percutaneous CT fluoroscopy-guided transpedicular approach with local anesthesia. In addition, sex, age, body mass index (BMI), thoracic level, related pathology, and procedure-related complications were also recorded. Results. A total of 57 patients (24 females, 33 males) were included. Mean age was 58.6 ± 15.5 years. No complications during CT fluoroscopy-guided gold fiducial marker placement were recorded. Intraoperative localization was successful in all patients. Mean BMI was 32.98 kg/m2 (range, 18.63-56.03 kg/m2), and 63% of patients were obese (>30 kg/m2). T7 (n = 11) was the most often marked vertebral body, followed by T10 (n = 10) and T6 (n = 7). The most cranial and most caudal levels marked were T2 and T12, respectively. Conclusion. Preoperative CT fluoroscopy-guided percutaneous gold fiducial marker placement is safe, feasible, and accurate. The resulting facilitated localization of the intended thoracic level of surgery can reduce the length of surgery and prevent wrong-level surgery. Further studies are needed to evaluate in the effect on exposure to radiation and quantify the difference in operating room time. Level of Evidence: 4